'Saviors' [compact disc] (Reprise, 2024)
Amazingly, Saviors represents Green Day's 14th studio album, yet somehow this enduring power trio, Billie Joe Armstrong, Tré Cool, and Mike Dirnt, remain devoted to their defiant craft that has fueled their career-long destruction of every boundary bestowed on the genre, and landed three East Bay punks in the Rock n Roll Hall of Fame. The album was recorded in both London and Los Angeles under the audacious ear and Rock prowess of Green Day's longtime friend & collaborator, Rob Cavallo.